Climate change vulnerability in cities: The case of Hamburg - Julia Rose; Christina Benita Wilke (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2015)
The vulnerability index presented in this paper is a tool to measure the vulnerability of different city areas related to flooding. The index is applied to the boroughs of the City of Hamburg. The city faces three different kinds of flood risks: storm surges, inland flooding and heavy rainfall. The presented index provides a basis for decision making about where to support or initiate appropriate adaptation measures. It is based on data from official statistics. Thus, it can easily be transferred to other regions and additional information can easily be added.
Keywords: 330; storm surges; inland flooding; heavy rain; social vulnerability; economic vulnerability